Hydrogen‐Bond‐Modulated Nucleofugality of SeIII Species to Enable Photoredox‐Catalytic Semipinacol Manifolds. Issue 49 (9th November 2022) - Park, Sooyoung; Dutta, Amit K.; Allacher, Carina; Abramov, Anton; Dullinger, Philipp; Kuzmanoska, Katerina; Fritsch, Daniela; Hitzfeld, Patrick; Horinek, Dominik; Rehbein, Julia; Nuernberger, Patrick; Gschwind, Ruth M.; et al.
Abstract: Chemical bond activations mediated by H‐bond interactions involving highly electronegative elements such as nitrogen and oxygen are powerful tactics in modern catalysis research. On the contrary, kindred catalytic regimes in which heavier, less electronegative elements such as selenium engage in H‐bond interactions to co‐activate C−Se σ‐bonds under oxidative conditions are elusive. Traditional strategies to enhance the nucleofugality of selenium residues predicate on the oxidative addition of electrophiles onto Se II ‐centers, which entails the elimination of the resulting Se IV moieties. Catalytic procedures in which Se IV nucleofuges are substituted rather than eliminated are very rare and, so far, not applicable to carbon‐carbon bond formations. In this study, we introduce an unprecedented combination of O−H⋅⋅⋅Se H‐bond interactions and single electron oxidation to catalytically generate Se III nucleofuges that allow for the formation of new C−C σ‐bonds by means of a type I semipinacol process in high yields and excellent selectivity. Abstract : A photoredox catalytic 1, 2‐carbon‐shift manifold is enabled by an unprecedented OH⋅⋅⋅Se III hydrogen bond co‐activation of C−Se σ‐bonds. While traditional oxidative methods for the activation of C−Se σ‐bonds proceed through Se IV intermediates and commonly result in rapid elimination of the Se IV residue, this protocol facilitates, for the first time, the stereospecific substitution of Se III nucleofuges by carbon nucleophiles.